Analysis of the fractal properties of silica aerogels using diffusion‐limited aggregation. Issue 1 (25th January 2021) - Abdusalamov, Rasul; Itskov, Mikhail; Milow, Barbara; Rege, Ameya
Abstract: Silica aerogels are highly porous solids with very low densities and thermal conductivities. Their high porosity results in a fractal morphology which has a strong influence on mechanical properties. In this work, the diffusion‐limited cluster aggregation (DLCA) method is implemented to model silica aerogel aggregates. A preliminary model based on this approach demonstrates good agreement with experimental data [1]. The influence on the fractal properties of different input parameters as for example the particle size is investigated. Moreover, the resulting geometries are compared to fractal features of silica aerogels determined by experimental data from small angle X‐ray scattering (SAXS). The mechanical response of these aggregation models is analyzed by a finite element analysis (FEA) for the generated representative volume elements (RVE). The effect of varying densities on the mechanical properties, for e.g., Young's modulus, is further elucidated.